Development of a Monte-Carlo Evaporation Code for Multiple-Fragment Emission - Nicolis, N. G. (HNPS Advances in Nuclear Physics, 2021)
An extended Hauser-Feshbach approach has been employed in a multi-step Monte-Carlo evaporation code designed to study the de-excitation of highly excited compound nuclei. The code is intended to account for emission of light particles (γ, n, ^1,2,3H, ^3-6He) and intermediate mass fragments in their ground and excited states (particle-bound or unbound). As a study case, we consider the decay of the compound nucleus ^120Te^* at excitation energy 100, 200 and 300 MeV. First chance decay widths are compared with treatments based on the Weisskopf and the s-wave approximation. Preliminary calculations are compared with experimental isotopic yields of intermediate mass fragments emitted in E/A = 50 MeV ^4He + ^116,124Sn → ^120,128Te^* reactions.